Nigerian external debt crisis : its management - Olukoshi, Adebayo O.; Nigerian Institute of International Affairs (Lagos : Malthouse Press, 1990)
This book is a proceeding of a seminar organized by the Nigerian Institute of International Affairs in February 1988. The book discusses external debt management within the context of Nigeria. Issues covered include origins and dimension of Nigeria's external debt; negotiations with London and Paris club; refinancing and servicing; debt-equity conversion among other topics
"Published in co-operation with and on behalf of The Nigerian Institute of International Affairs"--T.p. verso.
"Nigeria's external debt: an annotated bibliography, J.A. Oni": p. [210]-215.
Includes bibliographical references and index.
lje 18/07/16
Loans
Keywords: Debts, Management; Debts, External; Nigeria